2016
DOI: 10.3389/fnins.2015.00524
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of BALB/c Mice to Diesel Engine Exhaust Origin Secondary Organic Aerosol (DE-SOA) during the Developmental Stages Impairs the Social Behavior in Adult Life of the Males

Abstract: Secondary organic aerosol (SOA) is a component of particulate matter (PM) 2.5 and formed in the atmosphere by oxidation of volatile organic compounds. Recently, we have reported that inhalation exposure to diesel engine exhaust (DE) originated SOA (DE-SOA) affect novel object recognition ability and impair maternal behavior in adult mice. However, it is not clear whether early life exposure to SOA during the developmental stages affect social behavior in adult life or not. In the present study, to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Several studies examined the effects of diesel exhaust inhalational exposures on mRNA levels of glutamatergic receptors. In a study of diesel exhaust exposure of mice from GD14 to PND21, glutamate concentrations in hypothalamus were increased to the same extent by diesel exhaust alone and in conjunction with secondary organic aerosols (85). In a study of diesel injected subcutaneously at GD 6, 9, 12, 15 and 18, a slight reduction was found in NR2A receptor mRNA in hippocampus in offspring at 10 weeks of age (52).…”
Section: Potential Mechanisms Of Cognitive Impairmentmentioning
confidence: 99%
“…Several studies examined the effects of diesel exhaust inhalational exposures on mRNA levels of glutamatergic receptors. In a study of diesel exhaust exposure of mice from GD14 to PND21, glutamate concentrations in hypothalamus were increased to the same extent by diesel exhaust alone and in conjunction with secondary organic aerosols (85). In a study of diesel injected subcutaneously at GD 6, 9, 12, 15 and 18, a slight reduction was found in NR2A receptor mRNA in hippocampus in offspring at 10 weeks of age (52).…”
Section: Potential Mechanisms Of Cognitive Impairmentmentioning
confidence: 99%
“…In that study we have showed that GAD67 de ciency may be associated with glutamate/GABA imbalance in autistic brain. We have also reported that early life exposure of BALB/c mice to DE-SOA may affect their late-onset hypothalamic expression of social behavior related genes (ERα and oxytocin receptor) and induced impaired social behavior [27]. Taken together, environmental factors such as maternal infection, nutrition, antenatal care, education, drug usage and exposure to chemicals or pollutants during pregnancy are risk factors for ASD.…”
Section: Discussionmentioning
confidence: 83%
“…We have also established the neonatal animal model for early detection of environmental pollutant-induced learning disability and reported that DE-SOA impairs olfactory-based spatial learning activity in preweaning mice [26]. In addition, we have showed that early life exposure to DE-SOA impaired social behavior and alteration in social behavior related gene expression in the hypothalamus of adult male BALB/c mice [27]. Recently, we have developed valproic acid (VPA)-induced autism model rats and showed that reduction of gamma amino butyric acid (GABA) synthetic enzyme glutamic acid decarboxylase (GAD) 67 protein in both male and female VPA-exposed rats resulting in imbalance of glutamate/GABA was the possible mechanism for ASD [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles, a systemic inflammation mediator, and cytokines are linked to a lesion of cerebral tissue and results in neurological damage, which has been proposed in the literature (Harris et al, ). After previous studies have illustrated that particles have adverse cardiopulmonary effects, research about the CNS effect was reported recently (Liu et al, ; Win‐Shwe et al, ).…”
Section: Particles‐induced Detrimental Effects On Cnsmentioning
confidence: 99%
“…Animal experimental data illustrated that PM can cause a neurodevelopmental disorder. When male mice where exposured to SOAs during the neurodevelopmental stage, male adult mice were weak in social behavior including social novelty preference and social interaction (Win‐Shwe et al, ). In utero exposure to high‐concentrated DEP affects spatial learning and the memory of male offspring, with a reduced NMDAR expression in the hippocampus.…”
Section: Particles‐induced Detrimental Effects On Cnsmentioning
confidence: 99%